Teaching ‘Ajāib in Philippine Schools: Princess Urduja and The Power of Imagination - Isaac Donoso (Journal of Pesantren and Diniyah Studies, 2026)
Why did a tale narrated by a 14th century Maghrebi traveler influence modern Philippine history? Why were Filipino children learning Arabic mirabilia (‘ajā’ib) tales in schools to pass grades in Philippine history? Why was an Arabic text written by the Andalusian Ibn Juzayy al-Garnāṭī (1321-1357) in the Western Mediterranean material to teach to 20th century Southeast Asian students? This paper aims to clarify myth and history in narrating the origins of pre-Hispanic Philippines, and how Arabic sources influenced historiography to the point of considering what part of ‘ajā’ib literature (mirabilia) as historical facts. Using a historical research design and document analysis, this study found that the story of Princess Urduja from the fanciful kingdom of Tawalisi received great attention indeed, from official to popular culture, from professional history to political representation. We inquire into the reasons for the great pedagogical success of this medieval Arabic tale in the Philippine curriculum, and into the reality behind ideological and postcolonial agency towards empowerment through imagination.